Non-aggregated Aβ25-35 Upregulates Primary Astrocyte Proliferation In Vitro - Ohki, Elise C.; Langan, Thomas J.; Rodgers, Kyla R.; Chou, Richard C. (Frontiers in Cellular Neuroscience, 2017)
Amyloid beta (Aβ) is a peptide cleaved from amyloid precursor protein that contributes to the formation of senile plaques in Alzheimer’s disease (AD). The relationship between Aβ and astrocyte proliferation in AD remains controversial. Despite pathological findings of increased astrocytic mitosis in AD brains, in vitro studies show an inhibitory effect of Aβ on astrocyte proliferation. In this study, we determined the effect of the active fragment of Aβ (Aβ25-35) on the cell cycle progression of primary rat astrocytes. We found that Aβ25-35 (0.3-1.0 ug/ml) enhanced astrocyte proliferation in vitro in a time- and concentration-dependent manner. Increased DNA synthesis by Aβ25-35 was observed during the S phase of the astrocyte cell cycle, as indicated by proliferation kinetics and BrdU immunocytochemical staining. Aggregation of Aβ25-35 abolished the upregulatory effect of Aβ on astrocyte proliferation. Further examination indicated that Aβ25-35 affected astrocyte proliferation during early or mid-G1 phase but had no effect on DNA synthesis at the peak of S phase. These results provide insight into the relationship between Aβ25-35 and astrocyte cell cycling in AD.